GAMBARAN KEPUASAN PASIEN PENGGUNA KARTU BPJS DI POLI RS SWASTA PEKANBARU - MHD. Ali Safitroh; Erwin Erwin; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Health is a basic human needs to be able to live a productive, decent and patient satisfaction BPJS card users is oneof the main indicators to know whether or not the service of RS. This research aims to know the description ofpatient satisfaction BPJS card users in Poly RS Private Pekanbaru with adescriptive quantitative research design. Theresearch sample is 100 people respondents is taken based on the criteria of inclusion of non probability samplingusing a technique that is purposive sampling. Measuring instrument used was a questionnaire to measure patientsatisfaction BPJS card users. The results showed 100 people from respondents who researched most patients basedon age level is adult end end 36-45 year i.e. as many as 27 people respondents (27%), sex women 54 peoplerespondents (54%), high school education 52 those respondents (52%),Private job 28 respondents (28%). Patientsatisfaction was based on a dimension of tangibles satisfied 88 respondents (88%) people, the less satisfied amounted to5 respondents (5%), reliability of patients satisfied people 69 respondents (69%), less satisfied 29 respondents (29%),responsiveness (91 people satisfied respondents 91%), less satisfied 4 respondents (4%), assurance satisfied 92 peoplerespondents (92%), less satisfied three people respondents (3%), 66 people satisfied emphaty respondents (66%), lesssatisfied 31 respondents (31%). Thus obtained a majority of patients BPJS card users were satisfied with the servicesprovided at the in poly RS Syafira Pekanbaru is as much as 86(86%). Advice so that more hospitals improve patientsatisfaction was created primarily in order for card users BPJS.Keywords: BPJS, Patient Satisfaction,Respondent